[T]hat Monstrous Machine of his: The Machine Metaphor in John Clelands Memoir of a Woman of Pleasure - Choedphong Uttama (My University, 2021)
Abstract John Cleland’s Memoir of a Woman of Pleasure (1748–49), commonly known as Fanny Hill , is regarded as the first pornographic novel in English literature. Its description of sexual activities is explicit but its language is not coarse. It employs a wide range of metaphors to refer to both sexual acts and genitalia and the metaphor used most frequently to refer to the penis is “the machine.” The machine metaphor will be the focus of this paper, which aims to argue that the machine metaphor carries two meanings. The first is the machine as one of military metaphors common in erotica since sexual acts have long been represented as battles. Female sexual pleasure, portrayed in this novel, depends on the state of being destroyed or conquered by a large machine. The second usage of the military metaphor suggests the strong affiliation between the penis and a hydraulic machine – the hydraulic penis —as this paper will call it. That is, female sexual pleasure is not only entwined with the state of being ruined but also with a fluid flow.
Keywords: Literature: history, themes, analysis